Cascading effects of belowground predators on plant communities are density‐dependent. Issue 19 (12th September 2015) - Thakur, Madhav Prakash; Herrmann, Martina; Steinauer, Katja; Rennoch, Saskia; Cesarz, Simone; Eisenhauer, Nico
Abstract Soil food webs comprise a multitude of trophic interactions that can affect the composition and productivity of plant communities. Belowground predators feeding on microbial grazers like Collembola could decelerate nutrient mineralization by reducing microbial turnover in the soil, which in turn could negatively influence plant growth. However, empirical evidences for the ecological significance of belowground predators on nutrient cycling and plant communities are scarce. Here, we manipulated predator density (Hypoaspis aculeifer: predatory mite) with equal densities of three Collembola species as a prey in four functionally dissimilar plant communities in experimental microcosms: grass monoculture (Poa pratensis), herb monoculture (Rumex acetosa), legume monoculture (Trifolium pratense), and all three species as a mixed plant community. Density manipulation of predators allowed us to test for density‐mediated effects of belowground predators on Collembola and lower trophic groups. We hypothesized that predator density will reduce Collembola population causing a decrease in nutrient mineralization and hence detrimentally affect plant growth. First, we found a density‐dependent population change in predators, that is, an increase in low‐density treatments, but a decrease in high‐density treatments. Second, prey suppression was lower at high predator density, which caused a shift in the soil microbial community by increasing the fungal: bacterial biomass ratio, and an increase of nitrification rates, particularly in legume monocultures. Despite the increase in nutrient mineralization, legume monocultures performed worse at high predator density. Further, individual grass shoot biomass decreased in monocultures, while it increased in mixed plant communities with increasing predator density, which coincided with elevated soil N uptake by grasses. As a consequence, high predator density significantly increased plant complementarity effects indicating a decrease in interspecific plant competition. These results highlight that belowground predators can relax interspecific plant competition by increasing nutrient mineralization through their density‐dependent cascading effects on detritivore and soil microbial communities.